2004
DOI: 10.3748/wjg.v10.i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Does surgical resection of hepatocellular carcinoma accelerate cancer dissemination?

Abstract: AIM:This study was to investigate whether surgery could increase cancer dissemination and postoperative recurrence in patients with hepatocellular carcinoma (HCC) by detection of human α-fetoprotein messenger RNA (hAFP mRNA). hAFP mRNA in the peripheral blood of patients with HCC has been considered as a surrogate marker for circulating tumor cells. METHODS:Eighty-one consecutive patients who underwent curative resection for HCC entered this prospective cohort study. We examined hAFP mRNA from the peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…By applying high-resolution deconvolution microscopy, that allows the visualization of Cx signal within tumor testis, we proposed Cx43 delocalization as an early event associated with uncontrolled cell proliferation and a neoplastic marker of testis tumorisation since this aberrant Cx localization preceded down-regulation of Cx protein levels in a mouse testis cancer [169]. Other authors reported in patients who have undergone curative resection for hepatocellular carcinoma (HCC) that the reduced Cx32 mRNA expression in noncancerous liver tissues may play a significant role in the prediction of postoperative recurrence of this cancer [223].…”
Section: Connexin: Diagnostic Marker Of Carcinogenesismentioning
confidence: 97%
“…By applying high-resolution deconvolution microscopy, that allows the visualization of Cx signal within tumor testis, we proposed Cx43 delocalization as an early event associated with uncontrolled cell proliferation and a neoplastic marker of testis tumorisation since this aberrant Cx localization preceded down-regulation of Cx protein levels in a mouse testis cancer [169]. Other authors reported in patients who have undergone curative resection for hepatocellular carcinoma (HCC) that the reduced Cx32 mRNA expression in noncancerous liver tissues may play a significant role in the prediction of postoperative recurrence of this cancer [223].…”
Section: Connexin: Diagnostic Marker Of Carcinogenesismentioning
confidence: 97%
“…We think surgical resection of HCC may caused HCC cells spreading into peripheral blood shortly, but it is not concerning with recurrence and metastasis of HCC, just as the report from Sheen's [23]. HCC tumor vaccines may also play important role in clearance of these circulating HCC cells which may concern with HCC recurrence or metastasis, the further study is on the way [24,25,26].…”
Section: Discussionmentioning
confidence: 95%
“…14 Most CTCs may die in the blood by various host immune and nonimmune defenses, and can be destroyed by mechanical forces including turbulence and the trauma associated with vascular adhesion and transcapillary passage, or lysed by lymphocytes, monocytes, natural killer cells. 3 Other tumor cells may escape these defense mechanisms, and migrate to a new site where they adhere to the walls of the capillary system of a new organ and form new metastatic foci. Early detection of CTCs may help to assess the stage of the patients' diseases and prognosis as well as recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of those who undergo resection develop recurrence within 3 years. 2,3 Five-year survival rate of patients undergoing hepatic resection and orthotopic liver transplantation is 17% to 50% and 20% to 36%, respectively. 2,4 Patients detected early is up to 86.4% with the similar treatments.…”
mentioning
confidence: 99%